Pengobatan Suportif Vitamin D Mempercepat Konversi Sputum dan Perbaikan Gambaran Radiologis Penderita T uberkulosis - Siswanto, Siswanto; Sumarno, Sumarno; Jane, Yani; Widayanti, Oeryana Agustin; Muktiati, Nunuk Sri (Jurnal Kedokteran Brawijaya, 2009)
Pulmonary T uberculosis remains  as a major health problem in  South East Asia as well as Indonesia.  The failure  of  tuberculosis  treatment  is  mostly  due  to  drop-out  and  multiple  drugs  resistant.  Previous  study  showed that  Vitamin  D  increase  the  intracellular  cathelicidin  which  has  potency  to  kill  the  Mycobacterium tuberculosis. This research was aimed to identify the effect of Vitamin D as supportive treatment  on the improvement of sputum  conversion,  radiographic  finding  and  TNF-α  serum  concentration.  A  Double-blind randomized  control trial  was  used  in  two  random  allocated  patient  group  with  standard  tuberculosis  treatment.   The  first  group  was treated  with Vitamin  D (800  iu/day)  while the  other was not. Subjects were evaluated using three  parameters i.e.  sputum  conversion,  radiographic  finding  and  TNF-α  serum  concentration.  Compared to  the  group  without vitamin  D  supplementation,  group  with  vitamin  D  has  higher  proportion  of  sputum  conversion  in  the  first  month (67%    vs. 34%, p=0,04) and second month (95%  vs. 77%, p=0,18).    Improvement  in  radiographic  findings  in the  group with vitamin D is  also higher in  the  first  month (67%  vs. 18%, p=0,02) and second month (76%    vs. 45%,  p=0,06).    There is  a  significant  difference  in  the  level  of  25-dihidroxyvitamin  D between  two  groups (p=0,00). However,  there  is  no significant difference in  the  level  of TNF-α between two  groups (p=0,76) after two  months.